Ontologies of processes of intelligent management of the production of entomophages - Chernova, I.; Lysenko, V. (Energy and Automation, 2023)
The article deals with the ontologies of processes of intelligent management of the production of entomophages for biological protection of plants based on the application of the results of own research regarding the development and implementation in this production of i data mining based on neural networks, fuzzy logic, semantic modeling, cognitive and correlation-regression analysis.The purpose of the work – increasing the efficiency the processes of management of the production of entomophages.The object of study is the process of structuring knowledge regarding the processes of intelligent management of the production of entomophages. Methods of research – ontological approach, system analysis, results of own research, software environment Visual Understanding. Ontologies of processes have been developed: intelligent management of entomophages production, intelligent decision-making support in production management, use of artificial intelligence methods in production management; the ontology of knowledge in the processes of intelligent decision-making support in production management, the meta-ontology of the processes of intelligent production management. The destinations of the ontologies, as well as the formalization of the meta-ontology of the processes of intelligent management of the production of entomophages, are presented.The results of the research are the basis for the creation of intelligent decision support systems, provide the integration of knowledge regarding the processes of managing the production of entomophages.Key words: ontologies, intelligent management processes, production of entomophages, methods of artificial intelligence